(untitled) - Bernhardsen, Tor (New York, NY., 2002)
The ultimate comprehensive introduction to GIS--now in an updated, expanded new edition. "This book is well designed, solidly constructed, and finely crafted; those who depend on it as they set out to explore our spatial world will be well served. . . . If we are to solve many of the problems facing us--in the cities, in the wild areas of the earth, in the atmosphere and the oceans, problems of the earth as a whole--we shall need the help of skilled users of GIS technology. If readers can master what is in this volume, they will be well started on this enterprise." --From the Foreword by Jack Dangermond,President of ESRI. From reviews of the previous edition: * "Comprehensive and easy to read. . . . This book tackles all the key issues that should be found in any introductory GIS course attempting to deliver an understanding of the technical concepts and the underlying information issues."--GIS Europe/GIS World. * "Clear and well presented. . . . of interest to both technical and nontechnical readers." --Mapping Awareness & GIS in Europe.
Keywords: Geographic information systems,Hệ thống thông tin địa lý